The etiology of hypertransaminasemia in Turkish children - Filiz Serdaroğlu; Tuğba Koca; Selim Dereci; Mustafa Akçam (Biomolecules & Biomedicine, 2016)
The aim of this study was to investigate the causes of elevated levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in children. We analyzed the medical records for children aged 3 months to 18 years who presented to the hospital with ALT >45 IU/L and/or AST >50 IU/L, between 2012 and 2014, for various reasons, including those not related to liver disease. In total, 281 children met the study criteria. This group comprised of 125 (44.5%) females and 156 (55.5%) males. At the presentation, the most common patient complaint was fatigue (53.4%), while 15.7% of the patients reported no symptoms. The most common findings on the physical examination were jaundice and hepatomegaly. In 15% of the cases, the findings were normal. According to the diagnosis, the most common cause of the elevated transaminases were infections (34%), with hepatitis A virus (HAV) infection as the leading cause (18.9%). Drug-induced liver injury (DILI) was the cause in 18.1% of the cases and non-alcoholic fatty liver disease (NAFLD) in 11.1%. The highest transaminase levels were associated with HAV infection, while DILI and NAFLD caused only slightly elevated transaminases. Overall, our results show that the elevated transaminases in children are most often caused by infections, DILI, and NAFLD. In a majority of cases, elevated ALT and AST indicate liver disease, however, they could also be associated with conditions other than liver damage. Additionally, the elevated enzymes can be detected in completely healthy individuals.